Implementation Of The Double Exponential Smoothing Method In Determining The Planting Time In Strawberry Plantations - Fadly Shabir; Ahmad Irfan Abdullah; Billy Eden William Asrul; Sitti Alifah Amilhusna Nur (Jurusan Teknik Informatika, 2022)
Purpose: This research aims to provide recommendations for planting season based on predictions of rainfall, air temperature, and wind speed based on the website.Design/methodology/approach: This study implemented the Double exponential smoothing to predict rainfall, air temperature, and monthly wind speed one year in the future using past data.Findings/result: This study has succeeded in providing recommendations for planting season. Based on the results of the accuracy calculation between the prediction results and the actual data using the Mean Absolute Percetage Error (MAPE), each has a forecast error value of 30.69% for rainfall, 0.63% air temperature, and 5.89% wind speed. Originality/value/state of the art: Research related to the application of Double exponential smoothing to determine the planting period. Based on the results of the accuracy calculation between the prediction results and the actual data using Mean Absolute Percetage Error (MAPE), this has never been done in previous studies.